970. Emerging Pathogen Candida auris Evades Neutrophil Attack. (26th November 2018) - Johnson, Chad; Davis, J Muse; Huttenlocher, Anna; Kernien, John; Nett, Jeniel
Abstract: Background: Candida auris, an emerging fungal pathogen, causes hospital-associated outbreaks of invasive candidiasis with mortality near 60%. Little is known about the pathogenesis of this species that has newly arisen in the last 10 years, and it is unclear why this species is rapidly spreading worldwide. Neutrophils, critical for control of invasive candidiasis, kill fungi through phagocytosis or the release of neutrophil extracellular traps (NETs), which are structures of DNA, histones, and proteins with antimicrobial activity. The objective of this study was to delineate the neutrophil response to C. auris . Methods: We examined interactions of human neutrophils with C. auris and included C. albicans for comparison. Neutrophil– Candida interactions were visualized by time-lapse fluorescent microscopy and scanning electron microscopy (SEM). We utilized oxidative stress indicator CM-H2DCFDA to measure the generation of reactive oxygen species (ROS) in neutrophils. NET formation was quantified by Sytox Green staining and assessed by SEM and immunofluorescent labeling of NET-associated proteins. Fungal viability was evaluated using microbiological counts and viability stains. We utilized a zebrafish larvae infection model to evaluate neutrophil– Candida interactions in vivo. Results: Imaging revealed the phagocytosis of C. albicans by human neutrophils followed by the formation of NETs. In contrast, neutrophils encountering C. auris rarely engaged in phagocytosis or produced NETs. By Sytox Green staining, C. auris triggered negligible NET release by human neutrophils, with levels 7-fold lower when compared with C. albicans (Figure A). C. auris did not induce neutrophils to generate ROS, a key signaling mechanism for NET formation. The ineffective neutrophil response to C. auris correlated with diminished fungal killing (Figure B). Imaging of neutrophils in a zebrafish model of invasive candidiasis revealed the recruitment of approximately 50% fewer neutrophils in response to C. auris when compared with C. albicans (Figure C). Conclusion: C. auris evades neutrophils by altering multiple aspects of their usual anti-candidal responses. We propose that this diminished innate immune response may contribute to the unexpected virulence of C. auris. Disclosures: All authors: No reported disclosures.